Development of a New Internally Controlled One-Step Real-Time RT-PCR for the Molecular Detection of Enterovirus A71 in Africa and Madagascar - Volle, Romain; Joffret, Marie-Line; Ndiaye, Kader; Fernandez-Garcia, Maria Dolores; Razafindratsimandresy, Richter; Heraud, Jean-Michel; Rezig, Dorra; Sadeuh-Mba, Serge Alain; Boulahbal-Anes, Leila; Seghier, Mohamed; Deshpandeh, Jagadish M.; Bessaud, Maël; et al. (Frontiers in Microbiology, 2020)
Enterovirus A71 (EV-A71) is a leading cause of hand-foot-and-mouth disease (HFMD) and can be associated with severe neurological complications. EV-A71 strains can be classified into seven genogroups, A-H, on the basis of the VP1 capsid protein gene sequence. Genogroup A includes the prototype strain; genogroups B and C are responsible of major outbreaks worldwide, but little is known about the others, particularly genogroups E and F, which have been recently identified in Africa and Madagascar, respectively. The circulation of EV-A71 in the African region is poorly known and probably underestimated. A rapid and specific assay for detecting all genogroups of EV-A71 is required. In this study, we developed a real-time RT-PCR assay with a competitive internal control. The primers and TaqMan probe specifically target the genomic region encoding the VP1 capsid protein. Diverse EV-A71 RNAs were successfully amplified from the genogroups A, B, C, D, E, and F, with similar sensitivity and robust reproducibility. Neither cross reaction with other EVs nor major interference with the competitive internal control was detected. Experimentally spiked stool and plasma specimens provided consistent and reproducible results, and validated the usefulness of the internal control for demonstrating the presence of PCR inhibitors in samples. The analysis in an African laboratories network of 1889 untyped enterovirus isolates detected 15 EV-A71 of different genogroups. This specific real-time RT-PCR assay provides a robust and sensitive method for the detection of EV-A71 in biological specimens and for the epidemiological monitoring of EV-A71 including its recently discovered genogroups.